Metal surface treatment agent, method for manufacturing metal material, and metal material

A metal surface treatment agent combining zirconium sources and silane coupling agents with specific ratios and content levels addresses the inadequacies of existing agents by providing superior coating adhesion and corrosion resistance, even under demanding conditions.

JP2025060180APending Publication Date: 2025-04-10NIHON PARKERIZING CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023170740
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Existing metal surface treatment agents, such as those described in Patent Documents 1, 2, and 3, fail to provide sufficient coating adhesion and corrosion resistance under high load and harsh evaluation conditions, such as cylindrical processing and composite cycle tests.

Method used

A metal surface treatment agent containing at least one zirconium source and at least one silane coupling agent with an amino group, with a specific mass ratio of Zr to Si and a Zr content of 1.2% by mass or more, is used to form a surface treatment coating on metal materials.

Benefits of technology

The proposed metal surface treatment agent achieves excellent coating adhesion and corrosion resistance not only in traditional folding and salt spray tests but also under high load and harsh conditions, such as cylindrical processing and composite cycle tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060180000001
    Figure 2025060180000001
  • Figure 2025060180000002
    Figure 2025060180000002
  • Figure 2025060180000003
    Figure 2025060180000003
Patent Text Reader

Abstract

To provide a metal surface treatment agent that is not only excellent coating adhesion and corrosion resistance in bending processing or a salt water spray test which have conventionally been required, but also excellent coating adhesion and corrosion resistance in a highly loaded severe evaluation condition which have been required in recent years, specifically in cylinder machining or composite cycle test.SOLUTION: An embodiment of the present invention is metal surface treatment agent. At least one kind of zirconium source (A) and at least one kind of silane coupling agent (B) are compounded in the metal surface treatment agent. The silane coupling agent (B) has an amino group. A ratio (WA / WB) of the content of Zr (WA) and the content of Si (WB) in the metal surface treatment agent is 0.18 to 2.34 in a mass ratio. A mass ratio (NA) of Zr to a non-volatile component of the metal surface treatment agent is 1.2 mass% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a metal surface treatment agent, a method for producing a metallic material, and a metallic material. [Background technology]

[0002] Conventionally, in the fields of steel, home appliances, building materials, automobiles, etc., chromium-based surface treatment agents, such as chromate treatment, which have excellent adhesion to metal materials and can impart excellent corrosion resistance to metal materials, have been used as temporary rust prevention treatments or as undercoat treatments for paint films. These chromium-based surface treatment agents are still widely used today. However, in view of recent trends in environmental regulations, there is a possibility that the use of chromium may be restricted in the future due to the toxicity of chromium, particularly its carcinogenicity, etc. In addition, as the development of chromium-free metal surface treatment agents has progressed, there is a demand for the development of metal surface treatment agents that have the same adhesion and corrosion resistance as chromate treatment agents even under more severe evaluation conditions with higher loads than previously required, and that can serve as an alternative to chromium-based surface treatment agents.

[0003] For example, Patent Document 1 discloses a metal surface treatment agent that does not contain chromium on a zinc-plated steel sheet, can impart excellent workability and corrosion resistance to a PCM steel sheet, and has excellent storage stability.

[0004] Furthermore, Patent Document 2 discloses a base treatment liquid capable of forming a base layer that can enhance the adhesion of an organic resin layer even on a zinc plating layer.

[0005] Furthermore, Patent Document 3 discloses an aqueous surface treatment agent which is environmentally friendly and chromium-free, yet when used as a paint base for precoated metal materials, gives precoated metal materials which have excellent paint adhesion (processing adhesion of the coating film), corrosion resistance, and coin scratch resistance, and which also have good storage stability. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2001-240979 A [Patent Document 2] JP 2016-108629 A [Patent Document 3] JP 2006-328445 A Summary of the Invention [Problem to be solved by the invention]

[0007] The coating formed by the metal surface treatment agent described in Patent Document 1 has a certain level of effectiveness in bending adhesion (0TT processing) and corrosion resistance (salt spray test) evaluations. However, under more severe evaluation conditions with higher loads, both adhesion and corrosion resistance are insufficient, and better performance is required.

[0008] In addition, the coating formed by the primer treatment solution described in Patent Document 2 has an effect of increasing adhesion to an organic resin layer such as polyethylene for the purpose of corrosion protection of the outer surface of the steel pipe, mainly for use in hot-dip galvanized steel pipes buried underground. However, as in Patent Document 1, under more severe evaluation conditions with higher loads, both adhesion and corrosion resistance are insufficient, and better performance is required. In addition, the amount of coating applied to hot-dip galvanized steel pipes is relatively high, which is economically disadvantageous.

[0009] The surface treatment agent described in Patent Document 3 has a certain level of effectiveness in corrosion resistance (salt spray test) and processing adhesion (2T bending test) evaluations. However, as with Patent Documents 1 and 2, under more severe evaluation conditions with higher loads, both adhesion and corrosion resistance are insufficient, and better performance is required.

[0010] Therefore, an object of the present invention is to provide a metal surface treatment agent that not only satisfies the paint adhesion and corrosion resistance in bending processing and salt spray tests that have been conventionally required, but also has excellent paint adhesion and corrosion resistance under highly stressful and severe evaluation conditions that have been required in recent years, specifically, cylindrical processing and combined cycle tests; a manufacturing method for a metal material having a surface treatment film using the same; and a metal material having a surface treatment film obtained by the manufacturing method. [Means for solving the problem]

[0011] One embodiment of the present invention is a metal surface treatment agent comprising at least one zirconium source (A) and at least one silane coupling agent (B), the silane coupling agent (B) having an amino group, The metal surface treatment agent is characterized in that the ratio (WA / WB) of the Zr content (WA) to the Si content (WB) in the metal surface treatment agent is 0.18 to 2.34 in mass ratio, and the mass ratio (NA) of Zr to the non-volatile content of the metal surface treatment agent is 1.2 mass% or more.

[0012] In the metal surface treatment agent of the above embodiment, the zirconium source (A) may contain zirconium carbonate. The zirconium source (A) blended in the metal surface treatment agent may be zirconium carbonate alone. A metal compound (C) containing at least one metal selected from the group consisting of Ti, W, V, Co, Mo, Ca, Mg and Li may be blended. At least one cationic or nonionic resin (D) selected from the group consisting of urethane resins, polyvinyl alcohol resins, polyvinylpyrrolidone resins, phenol resins and epoxy resins may be blended. The silane coupling agent (B) may have a primary amino group.

[0013] Another aspect of the present invention is a method for producing a metal material, comprising the steps of contacting a metal material with the metal surface treatment agent according to any one of the above aspects, and drying the metal surface treatment agent that has been in contact with the metal material to form a surface treatment film.

[0014] Yet another aspect of the present invention is a metallic material obtained by the method for producing a metallic material according to the above aspect. Effect of the Invention

[0015] According to the present invention, it is possible to provide a metal surface treatment agent that not only satisfies the paint adhesion and corrosion resistance in bending processing and salt spray tests that have been conventionally required, but also exhibits excellent paint adhesion and corrosion resistance under the highly stressful and severe evaluation conditions that have been required in recent years, specifically, cylindrical processing and combined cycle tests; a manufacturing method for a metal material having a surface treatment film using the same; and a metal material having a surface treatment film obtained by the manufacturing method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] Hereinafter, embodiments of the present invention will be described in detail. In this specification, the expression "a to b" in the explanation of a numerical range means that the range is from a to b, unless otherwise specified.

[0017] The metal surface treatment agent according to this embodiment, the method for producing a metal material having a surface treatment film using the same, and the metal material having a surface treatment film obtained by the production method will be described below.

[0018] <Metal surface treatment agent> The metal surface treatment agent according to the embodiment contains at least one zirconium source (A) and at least one silane coupling agent (B). The metal surface treatment agent according to the embodiment can form a film having excellent paint adhesion and corrosion resistance on the surface of a metal material. Each component contained in the metal surface treatment agent according to the embodiment is dissolved or dispersed in an aqueous medium described below. Hereinafter, the metal surface treatment agent according to this embodiment will be described in detail.

[0019] (Zirconium source (A)) The zirconium source (A) may be a zirconium carbonate. More specifically, the zirconium carbonate may be basic zirconium carbonate, zirconium oxycarbonate, ammonium zirconium carbonate, potassium zirconium carbonate, etc. These zirconium carbonates may be mixed alone to produce a metal surface treatment agent, or two or more types may be mixed to produce a metal surface treatment agent. In addition, the zirconium source (A) may be a nitrate, a sulfate, a carbonate, a hydrofluoride, an ammonium salt, a potassium salt, a sodium salt, etc. The zirconium source (A) may consist solely of zirconium carbonate.

[0020] (Silane coupling agent (B)) The silane coupling agent (B) has an amino group. The silane coupling agent (B) is not particularly limited as long as it is a silane coupling agent having an amino group. The amino group of the silane coupling agent (B) is not particularly limited, but may be a primary amino group, a secondary amino group, a tertiary amino group, etc., and among these, it is more preferable that the silane coupling agent (B) has a primary amino group. The silane coupling agent (B) may have only one amino group, or may have two or more amino groups. Examples of the silane coupling agent (B) include N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane, N-(aminoethyl)3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, etc. One or more of these silane coupling agents (B) may be blended into the metal surface treatment agent.

[0021] In the metal surface treatment agent according to this embodiment, the ratio (WA / WB) of the Zr content (WA) to the Si content (WB) is preferably 0.18 to 2.34 by mass, more preferably 0.26 to 2.34, and even more preferably 0.58 to 2.34. The mass ratio (NA) of Zr to the non-volatile content of the metal surface treatment agent according to this embodiment is preferably 1.2 mass% or more, more preferably 1.5 mass% or more, and even more preferably 2.0 mass% or more. The "non-volatile content" in the metal surface treatment agent refers to the substances remaining after the metal surface treatment agent is heated at 110°C for 2 hours.

[0022] <Other ingredients> The metal surface treatment agent according to this embodiment may contain only the zirconium source (A) and the silane coupling agent (B) as components other than the aqueous medium, but may further contain other components such as a metal compound (C), a cationic or nonionic aqueous resin (D), a surfactant, etc.

[0023] (Metal compound (C)) The metal compound (C) preferably contains at least one metal selected from the group consisting of Ti, W, V, Co, Mo, Ca, Mg, and Li. In other words, examples of the metal compound (C) include titanium compounds, tungsten compounds, vanadium compounds, cobalt compounds, molybdenum compounds, magnesium compounds, and lithium compounds. The titanium compound is not particularly limited as long as it is a compound containing titanium element, and examples thereof include hydrofluoric acid, ammonium titanium fluoride, titanium sulfate, titanium oxysulfate, potassium titanium oxyoxalate, and diisopropoxytitanium bis. The tungsten compound is not particularly limited as long as it is a compound containing tungsten element, and examples thereof include metatungstic acid, ammonium metatungstate, sodium metatungstate, paratungstic acid, ammonium paratungstate, and sodium paratungstate. The vanadium compound is not particularly limited as long as it is a compound containing vanadium element, and examples thereof include vanadium pentoxide, metavanadic acid, ammonium metavanadate, sodium metavanadate, vanadium oxytrichloride, vanadium trioxide, vanadium dioxide, vanadium oxysulfate, vanadium oxyacetylacetonate, vanadium acetylacetonate, vanadium trichloride, and the like. The cobalt compound is not particularly limited as long as it is a compound containing cobalt element, and examples thereof include cobalt chloride, chloropentaamminecobalt chloride, hexaamminecobalt chloride, cobalt chromate, cobalt sulfate, ammonium cobalt sulfate, cobalt nitrate, aluminum cobalt oxide, cobalt hydroxide, and cobalt phosphate. The molybdenum compound is not particularly limited as long as it is a compound containing molybdenum element, and examples thereof include molybdenum oxide, molybdic acid, ammonium molybdate, ammonium paramolybdate, and sodium molybdate. The magnesium compound is not particularly limited as long as it is a compound containing magnesium element, and examples thereof include magnesium nitrate, magnesium sulfate, magnesium carbonate, magnesium hydroxide, magnesium fluoride, magnesium ammonium phosphate, magnesium hydrogen phosphate, magnesium oxide, and the like. The lithium compound is not particularly limited as long as it is a compound containing lithium element, and examples thereof include lithium oxide, lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium sulfate, and lithium silicate. The metal surface treatment agent may contain one type of these inorganic compounds or two or more types of them.

[0024] When the metal surface treatment agent according to this embodiment contains a metal compound (C), the blending ratio of the metal compound (C) is not particularly limited, but it is preferable that the ratio (NC) of the total non-volatile concentration of the metal compound (C) in terms of metal to the non-volatile concentration of the metal surface treatment agent according to this embodiment is in the range of 1 to 20 mass %.

[0025] (Cationic or nonionic water-based resin (D)) The cationic or nonionic aqueous resin (D) (hereinafter simply referred to as "aqueous resin (D)") is not particularly limited as long as it is a cationic or nonionic aqueous resin, and is, for example, at least one selected from the group consisting of urethane resin, polyvinyl alcohol resin, polyvinylpyrrolidone resin, phenol resin, acrylic resin, and epoxy resin. The aqueous resin (D) may be a homopolymer such as a urethane resin, a polyvinyl alcohol resin, a polyvinylpyrrolidone resin, a phenol resin, an acrylic resin, or an epoxy resin; a modified product obtained by modifying the side chain of the homopolymer with another compound, or a copolymer obtained by combining two or more of these resins or modified products. The form of the water-solubilized aqueous resin (D) is not particularly limited, and the aqueous resin (D) may be water-soluble or water-dispersible (emulsion, dispersion).

[0026] When the metal surface treatment agent according to the present embodiment contains the aqueous resin (D), the blending ratio of the aqueous resin (D) is not particularly limited, but it is preferable that the ratio (ND) of the total non-volatile concentration of the aqueous resin (D) to the non-volatile content concentration of the metal surface treatment agent according to the present embodiment is in the range of 5 to 50 mass %.

[0027] (Surfactant) The surfactant may be cationic, anionic, amphoteric, nonionic, etc., and examples thereof include cationic surfactants such as alkylamine salts and alkyltrimethylammonium halides; anionic surfactants such as alkylsulfonate esters, polyoxyethylene alkylphenyl ether sulfates, sodium dodecyl diphenyl ether disulfonate, and sodium dodecyl sulfate; amphoteric surfactants such as alkylaminopropionate salts and alkyldimethylbetaines; nonionic surfactants such as polyoxyethylene alkylphenyl ethers, polyoxyalkylene fatty acid esters, fatty acid glycerin esters, and polyoxyethylene propylene glycol fatty acid esters; etc. These surfactants may be used alone or in combination of two or more.

[0028] (aqueous medium) The aqueous medium is not particularly limited as long as it contains 50% by mass or more of water, and may be a medium consisting of water alone or a mixture containing water and a water-miscible organic solvent. The water-miscible organic solvent is not particularly limited as long as it is miscible with water, and examples thereof include ketone solvents such as acetone and methyl ethyl ketone, alcohol solvents such as methanol, ethanol, isopropanol, ether solvents such as ethylene glycol monobutyl ether and ethylene glycol monohexyl ether, pyrrolidone solvents such as 1-methyl-2-pyrrolidone and 1-ethyl-2-pyrrolidone, etc. One of these water-miscible organic solvents may be mixed with water, or two or more of them may be mixed with water.

[0029] In the metal surface treatment agent according to the present embodiment, the mass ratio of Cr to the non-volatile content of the metal surface treatment agent is preferably 0 mass%. By setting the mass ratio of Cr to 0 mass%, the metal surface treatment agent according to the present embodiment can be used as a substitute for chromium-free or non-chromium chromium-based surface treatment agents, and thus the impact on the environment can be suppressed.

[0030] The metal surface treatment agent described above not only exhibits the paint adhesion and corrosion resistance in bending processing and salt spray tests that have been conventionally required, but also exhibits excellent paint adhesion and corrosion resistance in the highly stressful and severe evaluation conditions that have been required in recent years, specifically, in cylindrical processing and combined cycle tests.

[0031] <Metal surface treatment agent manufacturing method> The metal surface treatment agent according to this embodiment can be produced, for example, by mixing the zirconium source (A), the silane coupling agent (B), and, if necessary, other components in predetermined amounts in an aqueous solvent.

[0032] <Metallic material having surface treatment film and method for producing same> The manufacturing method of a metal material having a surface treatment film according to this embodiment (hereinafter simply referred to as "the manufacturing method according to this embodiment") includes a contacting step of contacting the above-mentioned metal surface treatment agent with the surface or on the surface of a metal material, and a drying step of drying the metal surface treatment agent contacted with the surface or on the surface of the metal material. This manufacturing method can provide a metal material having a film with excellent paint adhesion and corrosion resistance on the surface or on the surface. Note that the manufacturing method according to this embodiment may also include a degreasing step and / or a chemical conversion treatment step prior to the contacting step.

[0033] <Metal materials> The shape and structure of the metal material on which the film is formed are not particularly limited, and examples of the shape include plate and foil. The type of metal material is also not particularly limited, and examples thereof include steel materials (e.g., cold-rolled steel sheets, hot-rolled steel sheets, black-skinned materials, pickled steel sheets, high-tensile steel sheets, tool steels, alloy tool steels, spheroidized graphite cast iron, gray cast iron, etc.); plating materials, such as zinc-plated materials (e.g., electrolytic zinc plating, hot-dip zinc plating, aluminum-containing zinc plating, electrolytic zinc plating, zinc-nickel plating, zinc-cobalt plating, vapor deposition zinc plating, etc.), zinc alloy-plated materials (e.g., alloyed hot-dip zinc plating, Zn-Al alloy plating, Zn-Al-M alloy plating, etc.), and the like. g alloy plating, electrolytic zinc alloy plating, etc.), aluminum plated materials, nickel plated materials, tin plated materials, chrome plated materials, chrome alloy plated materials (e.g., Cr-Ni alloy plating, etc.); aluminum materials or aluminum alloy materials (e.g., 1000 series, 2000 series, 3000 series, 4000 series, 5000 series, 6000 series, aluminum castings, aluminum alloy castings, die-cast materials, etc.); copper materials or copper alloy materials; titanium materials or titanium alloy materials; magnesium materials or magnesium alloy materials, etc.

[0034] <Contact process> Examples of the contact method include, but are not limited to, spraying, immersion, roll coating, bar coating, curtain coating, spin coating, and combinations of these. The contact temperature and contact time are appropriately set depending on the composition and concentration of the metal surface treatment agent, but the contact temperature is usually within the range of 0° C. to 50° C., and the contact time is usually within the range of 1 second to 300 seconds.

[0035] <Drying process> The drying method is not particularly limited, and examples thereof include drying methods using known drying equipment such as a batch-type drying oven, a continuous hot air circulation drying oven, a conveyor-type hot air drying oven, an electromagnetic induction heating oven using an IH heater, etc. The drying temperature and drying time are appropriately set depending on the type of metal material and the composition or amount of the contacted metal surface treatment agent, but the drying temperature is usually within the range of 60° C. to 250° C., and the drying time is within the range of 1 second to 1800 seconds.

[0036] <Degreasing process> The degreasing method may be any method capable of removing grease and dirt, and examples thereof include known methods using solvent degreasing, alkaline or acidic degreasing agents, etc. When the contact step or chemical conversion treatment step is performed after the degreasing step, a step of washing the surface or the upper surface of the metal material with water may or may not be performed after the degreasing step and before the contact step or the chemical conversion treatment step. When washing with water is performed, the surface or the upper surface of the metal material may or may not be dried subsequently.

[0037] <Chemical conversion treatment process> The chemical conversion treatment step is not particularly limited as long as it is a treatment for forming a chemical conversion film, and examples thereof include a zirconium chemical conversion treatment step, a titanium chemical conversion treatment step, a nickel chemical conversion treatment step, a hafnium chemical conversion treatment step, a phosphate conversion treatment step, a chromate chemical conversion treatment step, and the like. After the chemical conversion treatment step and before the contact step, a step of washing the surface or the surface of the metal material with water may or may not be performed. If washing with water is performed, the surface or the surface of the metal material may or may not be dried subsequently. In addition, when a phosphate conversion treatment step using zinc phosphate is performed as the chemical conversion treatment step, a surface conditioning treatment step for the purpose of improving the reactivity of the phosphate conversion treatment may be performed on the metal material between the degreasing step and the phosphate conversion treatment step. As the surface conditioning treatment method, a known method can be used.

[0038] <Chemical conversion coating agent> The chemical conversion treatment step is carried out by contacting the chemical conversion treatment agent with the surface or on the surface of the metal material. Examples of the chemical conversion treatment agent include, but are not limited to, zirconium chemical conversion treatment agents, titanium chemical conversion treatment agents, nickel chemical conversion treatment agents, hafnium chemical conversion treatment agents, phosphate conversion treatment agents, and chromate chemical conversion treatment agents. The contact of the chemical conversion treatment agent can be performed by a known method, such as, but not limited to, an immersion treatment method, a spray treatment method, a pouring treatment method, or a combination thereof. The temperature or contact time of the chemical conversion treatment agent in each chemical conversion treatment step can be appropriately set depending on the type of chemical conversion treatment step, the concentration of the chemical conversion treatment agent, and the like.

[0039] <Surface treatment film> The mass of the surface treatment film formed on the surface of a metal material by the metal surface treatment agent is not particularly limited as long as the performance of the metal surface treatment agent of the present embodiment can be exhibited. For example, the mass of the surface treatment film is 0.05 g / m 2 More than 4g / m 2 It is preferable that the range is 0.05 g / m 2 More than 3g / m 2 It is more preferable that the content is within the following range:

[0040] Since the surface treatment film formed as described above has excellent paint adhesion, it can be used as an undercoat film for precoated metal materials which usually have one to three coating layers on top.

[0041] The precoated metal material is produced by forming an upper coating layer on the surface treatment film, i.e., the base coating, formed on the metal material using the metal surface treatment agent of this embodiment as described above. The upper coating layer can be formed by a coating method generally used for precoated steel sheets, such as a coating method in which a primer is applied to the base coating and dried, and then a top coat is applied, a coating method in which a top coat is applied directly without using a primer, or a method in which a laminate film is attached.

[0042] The primer is not particularly limited, and usually contains a resin and, if necessary, a color pigment, an anti-rust pigment, etc. The resin may be in any form, such as a water-based, solvent-based, or powder-based form, and the type of resin may be generally known, such as polyacrylic resins, polyolefin resins, polyurethane resins, epoxy resins, polyester resins, polybutyral resins, melamine resins, and fluorine resins, which may be used alone or in combination.

[0043] As the coloring pigment, known coloring pigments such as inorganic pigments such as titanium oxide, zinc oxide, zirconium oxide, calcium carbonate, barium sulfate, alumina, kaolin clay, carbon black, iron oxide, etc., and organic pigments can be used. As the rust-preventive pigment, generally known ones can be used, for example, phosphate-based rust-preventive pigments such as zinc phosphate, iron phosphate, aluminum phosphate, etc., molybdate-based rust-preventive pigments such as calcium molybdate, ammonium molybdate, barium molybdate, etc., vanadium-based rust-preventive pigments such as vanadium oxide, etc. Furthermore, defoamers, dispersion assistants, diluents for reducing the paint viscosity, etc. can be appropriately used.

[0044] The method of applying the primer is not particularly limited, and can be a commonly used method such as dipping, spraying, roll coating, air spraying, or airless spraying. The thickness of the applied primer is preferably 1 to 30 μm, and more preferably 2 to 20 μm, as a dry film thickness. The baking and drying conditions of the primer are not particularly limited, and can be, for example, 130 to 250° C. and 1 to 300 seconds.

[0045] The top coat is not particularly limited, and any of the usual top coats for painting can be used. That is, the top coat contains a resin and, if necessary, a coloring pigment, an anti-rust pigment, etc. The resin, coloring pigment, and anti-rust pigment can be the same as those used in the primer, and other optional components that can be used in the primer can also be used.

[0046] The method of application and baking conditions for the top coat may be the same as those for the primer. The thickness of the top coat, as a dry thickness, is preferably 3 to 50 μm, and more preferably 5 to 40 μm.

[0047] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can also be adopted. EXAMPLES

[0048] EXAMPLES Hereinafter, the present invention will be described with reference to examples and comparative examples, but the present invention is not limited to these.

[0049] <Preparation of metal surface treatment agent> The compositions of the metal surface treatment agents of Examples 1 to 33 and Comparative Examples 1 to 4 are shown in Table 1. Details of the symbols shown in the columns for zirconium source (A), silane coupling agent (B), metal compound (C), and water-based resin (D) in Table 1 are shown in Tables 2 to 5. Each metal surface treatment agent was prepared by mixing each component and a surfactant (polyetherified product of acetylene-based dialcohol) with deionized water. The non-volatile content concentration in each metal surface treatment agent was adjusted to 6%.

[0050] [Table 1]

[0051] [Table 2]

[0052] [Table 3]

[0053] [Table 4]

[0054] [Table 5]

[0055] <Preparation of evaluation samples> The test material was an aluminum-zinc alloy-plated steel sheet (hereinafter referred to as GL) (sheet thickness 0.35 mm, coating weight 50 g / m per side). 2 The degreasing treatment was carried out by spraying an alkaline degreasing agent [Fine Cleaner E6406 (manufactured by Nihon Parkerizing Co., Ltd.) dissolved in water to a mass concentration of 2%] at 60°C for 10 seconds. The surface of the test material was then washed with water and dried at 115°C for 20 seconds.

[0056] The coating amount was 100 mg / m2 for the test material that had been degreased, washed and dried. 2 Each metal surface treatment agent (each metal surface treatment agent of Examples 1 to 32 and Comparative Examples 1 to 4) was bar-coated so as to obtain a metal temperature of 80°C, and then the bar was dried in a drying furnace to obtain a test sample having a base coating.

[0057] Next, a commercially available primer paint (V-knit #200, manufactured by Nippon Paint Co., Ltd.) was bar-coated onto the test sample having the above-mentioned base coating so that the dry film thickness was 5 μm, and then the test sample was dried in a drying oven so that the metal temperature reached was 200°C, thereby producing a test sample having a primer coating.

[0058] Next, a commercially available topcoat paint (V-knit #500, manufactured by Dai Nippon Toryo Co., Ltd.) was bar-coated onto the test sample having the above primer film so that the dry film thickness was 15 μm, and then the test sample was dried so that the metal temperature reached was 220°C, thereby producing a test sample having a primer film, which was designated as evaluation samples No. 1 to 37.

[0059] <Evaluation method> The evaluation samples Nos. 1 to 37 prepared above were subjected to the following evaluations.

[0060] <Paint adhesion> (0T bending process) In accordance with the JIS-G3312 test method, a 0T bending test was performed on each evaluation sample at 20°C without using an inner spacer, and the state of coating film peeling after tape peeling was observed with the naked eye and evaluated in accordance with the following evaluation criteria. <Evaluation criteria> ◎ + : No peeling ◎: Peeling area less than 10% ○: Peeling area is 10% or more but less than 50% △: Peeling area is 50% or more and less than 80% ×: Peeling area 80% or more

[0061] <Paint adhesion> (Cylindrical processing) Each evaluation sample was set in a high-speed deep drawing tester (Tokyo Test Machinery Manufacturing Co., Ltd.) and subjected to a deep drawing test under the following conditions. A score of ◯ or higher was deemed to be a pass. Mold: Cylindrical, Mold dimensions: Blank diameter 110mmφ, Punch outer diameter 50mmφ, Die inner diameter 51.64mmφ, Punch R: 3mm, Clearance: 0.82mm, Processing speed: 40spm, Wrinkle holding pressure: 1kgf / cm 2 <Evaluation criteria> ◎ + : No wrinkles or peeling is visible ◎: Less than 5% wrinkles or peeling is visible ○: Wrinkles or peeling of 5% to 10% are visible △: Wrinkles or peeling of 10% to less than 40% are visually observed ×: 40% or more of wrinkles or peeling is visually observed

[0062] <Corrosion resistance> (Salt spray test) The coating of each evaluation sample was scratched with a cutter so that it reached the metal base material, and the salt spray test specified in JIS-Z2371 was carried out for 480 hours. The evaluation was carried out by measuring the width of the coating blister from the cut (maximum value on one side). In addition, the width of the coating blister from the edge (maximum value) was measured as an index of edge corrosion resistance. <Evaluation criteria - Cutting section> ◎ + : Less than 1 mm ◎: 1mm or more and less than 2mm ○: 2mm or more and less than 4mm △: 4mm or more and less than 6mm ×: 6mm or more <Evaluation criteria - end face> ◎ + : Less than 3 mm ◎: 3mm or more and less than 6mm ○: 6mm or more and less than 10mm △: 10mm or more and less than 15mm ×: 15mm or more

[0063] (Combined cycle test) The coating of each evaluation sample was scratched with a cutter so that the scratch reached the metal base material, and the combined cycle test specified in JIS-H8502 (JASO M609-91) was carried out for 180 cycles. The coating blister width (maximum value on one side) from the cut was measured and evaluated according to the following evaluation criteria. In addition, the coating blister width (maximum value) from the edge was measured as an index related to edge corrosion resistance, and evaluated according to the following evaluation criteria. <Evaluation criteria - Cutting section> ◎ + : Less than 1 mm ◎: 1mm or more and less than 2mm ○: 2mm or more and less than 4mm △: 4mm or more and less than 6mm ×: 6mm or more <Evaluation criteria - end face> ◎ + : Less than 3 mm ◎: 3mm or more and less than 6mm ○: 6mm or more and less than 10mm △: 10mm or more and less than 15mm ×: 15mm or more

[0064] The paint adhesion results, salt spray test results, and combined cycle test results for each evaluation sample are shown in Table 6. Each evaluation result of "◯" or higher was considered a pass.

[0065] [Table 6]

Claims

1. A metal surface treatment agent comprising at least one zirconium source (A) and at least one silane coupling agent (B), The silane coupling agent (B) has an amino group, In the metal surface treatment agent, the ratio (WA / WB) of the Zr content (WA) to the Si content (WB) is 0.18 to 2.34 in terms of mass ratio, A metal surface treatment agent, characterized in that a mass ratio (NA) of Zr to a non-volatile content of the metal surface treatment agent is 1.2 mass% or more.

2. 2. The metal surface treatment agent according to claim 1, wherein the zirconium source (A) comprises zirconium carbonate.

3. 2. The metal surface treatment agent according to claim 1, wherein the zirconium source (A) contained in the metal surface treatment agent is zirconium carbonate alone.

4. 2. The metal surface treatment agent according to claim 1, further comprising a metal compound (C) containing at least one metal selected from the group consisting of Ti, W, V, Co, Mo, Ca, Mg and Li.

5. 2. The metal surface treatment agent according to claim 1, further comprising at least one cationic or nonionic resin (D) selected from the group consisting of urethane resins, polyvinyl alcohol resins, polyvinylpyrrolidone resins, phenolic resins and epoxy resins.

6. 5. The metal surface treatment agent according to claim 4, further comprising at least one cationic or nonionic resin (D) selected from the group consisting of urethane resins, polyvinyl alcohol resins, polyvinylpyrrolidone resins, phenolic resins and epoxy resins.

7. 2. The metal surface treatment agent according to claim 1, wherein the silane coupling agent (B) has a primary amino group.

8. A step of contacting a metal material with the metal surface treatment agent according to any one of claims 1 to 7, and a step of drying the metal surface treatment agent that has been brought into contact with the metal material to form a surface treatment film. A method for producing a metal material having a surface treatment film, comprising the steps of:

9. A metallic material having a surface treatment film, obtained by the method for producing a metallic material according to claim 8.

Citation Information

Patent Citations

  • Roof of strong wind escaping type

    JP1998008629A

  • Non-chromate surface treating agent for pcm, pcm surface treatment method and treated pcm steel sheet

    JP2001240979A

  • JP328445A